Association Between Profile Characteristics and the Level of Aspiration of Women Dry Fish Wholesalers - P.S. Swathi Lekshmi, A.P. Dineshbabu (Indian Journal of Extension Education, 2022)
Over the last two centuries, women’s role in fisheries has been predominantly in the fish processing and marketing sectors. Processing is clearly the sub sector where women are most involved in fisheries, demonstrating a small majority of the workforce at 53 per cent but within an average of 11 to 75 per cent. However women are mostly 40 to 60 per cent of the workforce, with only Greece (11%) having markedly less than 40 per cent female involvement. (Elliot, 2002). Women’s involvement in the management and administration element of the sector is, at 39 per cent perhaps higher than might have been expected in what has notoriously been a male dominated preserve. However, this does not necessarily mean that women have made inroads into the senior management roles, and anecdotal evidence suggests that indeed women are generally not represented at the higher levels.